Association between thyroid dysfunction and venous thromboembolism: A systematic review and meta-analysis. Issue 11 (17th March 2023) - Wang, Yunmeng; Ding, Chaowei; Guo, Chang; Wang, Jingru; Liu, Suyun
Abstract : Background: Thyroid dysfunction plays an important role in the development of cardiovascular disease. However, its relationship with venous thromboembolism (VTE) remains unclear. We performed a meta-analysis of published cohort and case-control studies to investigate the association between thyroid dysfunction and VTE comprehensively. Methods: Three reviewers independently searched EMbase, PubMed, China national knowledge infrastructure, and Cochrane Library databases for relevant articles from the time of database establishment to 01 October 2022 and identified all studies on thyroid dysfunction and VTE as studies of interest. Of the 2418 publications retrieved, we identified 10 articles with 15 studies that met our selection criteria. Pooled ORs and 95% confidence intervals were calculated using fixed- or random-effect models. Results: We pooled 8 studies by a fixed-effect model, which suggested an increased risk of VTE in patients with (subclinical) hyperthyroidism (OR 1.33, 95% CI: 1.29–1.38). In the other 7 studies on patients with (subclinical) hypothyroidism, the risk was similarly increased when pooled by a random-effect model (OR 1.52, 95% CI: 1.23–1.89). After sensitivity analysis and risk of bias analysis, the risk of VTE was still increased in both (subclinical) hyperthyroidism (OR 1.322, 95% CI: 1.278–1.368) and (subclinical) hypothyroidism (OR 1.74, 95% CI: 1.41–2.16). Conclusion: Patients with thyroid dysfunction have an increased risk of VTE. Therefore, it is recommended to perform thyroid function screening routinely in patients at high risk of VTE.